2018
DOI: 10.1164/rccm.201712-2472oc
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a Host Response Assay, SeptiCyte LAB, for Discriminating Sepsis from Systemic Inflammatory Response Syndrome in the ICU

Abstract: SeptiCyte LAB appears to be a promising diagnostic tool to complement physician assessment of infection likelihood in critically ill adult patients with systemic inflammation. Clinical trial registered with www.clinicaltrials.gov (NCT01905033 and NCT02127502).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 32 publications
1
93
0
Order By: Relevance
“…In a multicohort discovery and validation study in ICU patients, SeptiCyte Lab showed significantly higher diagnostic accuracy for discriminating sepsis from SIRS than did procalcitonin (42). A recent multicohort trial of SeptiCyte Lab sponsored by its manufacturer in 447 ICU patients showed area under the receiver operating characteristic (ROC) curve (AUC) for discriminating sepsis from SIRS ranging from 0.82 to 0.89, with negative predictive values ranging from 89% to 94% (43). It showed a head-to-head AUC of 0.85 for SeptiCyte Lab versus 0.80 for procalcitonin in patients with both measurements.…”
Section: Transcriptomics In the Diagnosis Of Infectionsmentioning
confidence: 99%
“…In a multicohort discovery and validation study in ICU patients, SeptiCyte Lab showed significantly higher diagnostic accuracy for discriminating sepsis from SIRS than did procalcitonin (42). A recent multicohort trial of SeptiCyte Lab sponsored by its manufacturer in 447 ICU patients showed area under the receiver operating characteristic (ROC) curve (AUC) for discriminating sepsis from SIRS ranging from 0.82 to 0.89, with negative predictive values ranging from 89% to 94% (43). It showed a head-to-head AUC of 0.85 for SeptiCyte Lab versus 0.80 for procalcitonin in patients with both measurements.…”
Section: Transcriptomics In the Diagnosis Of Infectionsmentioning
confidence: 99%
“…Therefore, given the wide variety of pathogens that can cause disease, clinical microbiology laboratories could benefit from using the approach of "sepsis diagnostic panels" that combine detection of pathogens and key aspects of the patient's innate and systemic immune response. One novel approach is the Immunexpress SeptiCyte LAB assay, which produces a 4-gene expression bloodbased signature and discriminates viral and nonviral causes of systemic inflammation (35). Full review of this approach is beyond the scope of this review.…”
Section: Rapid Molecular Methods For the Diagnosis Of Sepsis And Bactmentioning
confidence: 99%
“…Combined analysis of leukocyte biomarkers has also been investigated. Finally, proteomics and transcriptomics have also been proposed to allow discrimination between bacterial and viral infection (Oved et al , ; Miller et al , ).…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%